2018
DOI: 10.17305/bjbms.2018.2318
|View full text |Cite
|
Sign up to set email alerts
|

Predictors and incidence of hospitalization due to respiratory syncytial virus (RSV)-associated lower respiratory tract infection (LRTI) in non-prophylaxed moderate-to-late preterm infants in Bosnia and Herzegovina

Abstract: Prematurity is a risk factor for respiratory syncytial virus (RSV)-associated lower respiratory tract infections (LRTIs), due to immature humoral and cell-mediated immune system in preterm newborns, as well as their incomplete lung development. Palivizumab, a humanized monoclonal antibody against the F glycoprotein of RSV, is licensed for the prevention of severe RSV LRTI in children at high risk for the disease. This study is a part of a larger observational, retrospective-prospective epidemiological study (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 43 publications
(67 reference statements)
0
8
0
1
Order By: Relevance
“…The lack of RSV detection in the air samples might be attributed to the small number of RSV-patients included in this study. Furthermore, the respiratory symptoms in RSV-infected patients usually appear around 3 days prior to hospital admission [ 62 , 63 ]. Therefore, the lack of sampling on day one of admission from RSV-patients’ room might have also reduced our ability to detect the virus in the air.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of RSV detection in the air samples might be attributed to the small number of RSV-patients included in this study. Furthermore, the respiratory symptoms in RSV-infected patients usually appear around 3 days prior to hospital admission [ 62 , 63 ]. Therefore, the lack of sampling on day one of admission from RSV-patients’ room might have also reduced our ability to detect the virus in the air.…”
Section: Discussionmentioning
confidence: 99%
“…22 Two studies found a significantly reduced risk of RSVH in late preterm multiple births 8 9 while three reports showed no difference in the proportion of multiple births compared with non-multiple births that were hospitalised with RSV. [23][24][25] Haerskjold et al 9 found that children of multiple birth born between 33-35 weeks and 36 wGA were associated with a decreased risk of RSVH (adjusted HR 0.56, 95% CI 0.40 to 0.78, p=0.001) and a similar trend of reduced RSVH risk was documented by Ambrose et al (HR 0.48; p=0.043). 8 The postulated rationale for the decreased risk was attributed to differences in provider or parental behaviour in the care of twins 8 and that preterm twins of advanced gestational age are otherwise healthy compared with their counterparts of lower gestational age.…”
Section: Commentarymentioning
confidence: 57%
“…22 Although rare, there have been reports of neuropsychiatric adverse events (AEs) in children including depression, anxiety, psychosis and suicidal ideation. 23…”
Section: Commentarymentioning
confidence: 99%
“…In addition, 10 studies were carried out prospectively, while 2 were carried out retrospectively. Of the 12 studies, 2 each were from Brazil, 15,16 Turkey, 17,18 Argentina, 19,20 and one each from Nepal, 21 Peru, 22 South Africa, 23 Bosnia and Herzegovina, 24 Iran, 25 and Mexico. 26 The majority of studies were conducted in the last decade except for one study conducted in 2002.…”
Section: Resultsmentioning
confidence: 99%